2023
DOI: 10.1177/08863687231192179
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Employee Resource Groups: Leader Experiences Driving Mutual Benefits for Employees and Employers

Steven Schlachter,
Skylar Rolf,
Theresa M. Welbourne

Abstract: Employee Resource Groups (ERGs), which bring together employees with shared identity or purpose, have been expanding around the globe. ERGs can be a recruiting and retention tool, providing member benefits of career growth, developing friends and providing expanded purpose at work. Given their popularity, they are of interest for researchers. Thus, we conducted a study focused on the ERG leader experience overall and the benefits to employees and employers offered by ERGs. We did this by conducting in-depth in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…ERGs can be particularly beneficial for immigrant employees by fostering a sense of community (Scully, 2009), providing opportunities for skill development and networking, and facilitating cultural exchange within an organization (Schlachter et al, 2023; Welbourne et al, 2015). A 2021 study by McKinsey and Company and https://LeanIn.org examined 423 organizations (12 million employees) and found that 35% of companies have increased support for ERGs.…”
Section: Practical Implications: Diversity and Inclusion Climate For ...mentioning
confidence: 99%
“…ERGs can be particularly beneficial for immigrant employees by fostering a sense of community (Scully, 2009), providing opportunities for skill development and networking, and facilitating cultural exchange within an organization (Schlachter et al, 2023; Welbourne et al, 2015). A 2021 study by McKinsey and Company and https://LeanIn.org examined 423 organizations (12 million employees) and found that 35% of companies have increased support for ERGs.…”
Section: Practical Implications: Diversity and Inclusion Climate For ...mentioning
confidence: 99%
“…The Organizations that aim to be inclusive incorporate ways to foster community among employees by creating safe spaces for marginalized groups, usually referred to as employee resource groups (ERGs; Schlachter et al, 2023). ERGs are a common practice, but they may not be present in every organization due to the organization's structure.…”
Section: Absence Of Career Support and Directionmentioning
confidence: 99%